CHARACTERISTIC OF EXPANSIVE CLAY SOIL (Case research at Bugel Village, Godong Subdistrict, Purwodadi Regency, Central Java Province) - Soedarsono Soedarsono; Pratikso Pratikso (International Conference on Coastal and Delta Areas, 2017)
Almost all civil constructions were built on the ground. However, not all soil types can be used for construction due to the load supporting capacity of the soil and the soil deformation that occurs for each different soil type. One type of soil that has many problems on its supporting capacity is expansive clay soil. It is a type of soil that has a mineral content that easily absorbs water in wet conditions and also release water easily in dry conditions so that is soil can swell and shrink in a relatively short time. The purpose of this research is to know expansive soil characteristic in Bugel Village, Godong District, Purwodadi Regency, Central Java Province covering physical and mechanical properties. Based on laboratory tests, the soil in Bugel Village has Waverage = 60.90%. From result of atterberg limit test obtained result LL = 90,75%; PL = 24.138%; SL = 23.759%; And PI = 66.612%. According to Raman with a PI of 66.612% already shows the soil is expansive ground. For Gravity Specific the results is 2,782, indicating the soil contains Montmorillonite minerals that have high passivity properties. The AASTHO classification of soil is incorporated into groups A-7-6 whereas for USCS classification is incorporated into CH zones and for English classification is entered into the zone between CV and CE. Of the three classifications can be drawn the clay soil area has a high plasticity value. For standard compaction test result, the characteristic value for maximum γunsat = 1,389 gr / cm2, γsat maximum = 1.78 gr / cm2, Woptimum = 31,46%, and n = 58,92%. And for soil swelling test can be seen the percentage of swelling is very high that is about 274%. Keywords: Soil Charactreristic, Expansive Clay Soil, Montmorillonite, Bugel Village.